Product liability law - Geistfeld, Mark Allen (Wolters Kluwer, 2022)
"Products liability casebook for law school students"--
This Titel is now published by Aspen Publishing
Keywords: Products liability / United States; Products liability / United States / Cases; Products liability; United States; Casebooks (Law); Trials, litigation, etc